Participative Finance, Microfinance, and Self Entrepreneurship in Morocco - Adil Zarfi (International Journal of Islamic Khazanah, 2022)
The main purpose of this study is to investigate the role of participative Finance and Microfinance in Morocco to enhance and empower entrepreneurship. The new banking law NÂ° 103-12 reinforces the legal framework. It offers an opportunity to the participative financial institutions to implement their products and participate in the financial inclusion strategy in Morocco, which can facilitate the access of VSMEs and auto entrepreneurs to several modes of financing. For this reason, it is necessary to determine the place of participative Microfinance in the ecosystem of participative Finance and the necessary conditions for its implementation. It is also necessary to know if the formal financial system is well designed to serve the financing needs of auto entrepreneurs in Morocco. The study proposes a conceptual framework to establish the relationship between participative Finance, Microfinance, and entrepreneurship in the case of auto-entrepreneur schemes. In this regard, it seems necessary to know the degree of importance of financial inclusion and if it is enough to empower the auto entrepreneurs, which also helps to determine the contribution of participative Finance and Microfinance in entrepreneurship. Understanding the overall socio-economic structures in Morocco will help determine the obstacles and level of awareness on the demand or supply side. It will help to know whether the Shariah-compliant products can meet on expectations of the VSEs segment. For this purpose, the perception and attitudes of auto entrepreneurs were analyzed using an online survey. A group of experts' perceptions was also analyzed using a qualitative approach, in which semi-structured interviews were conducted.Â